2021
DOI: 10.1111/clr.13714
|View full text |Cite
|
Sign up to set email alerts
|

Early bone formation in mini‐lateral window sinus floor elevation with simultaneous implant placement: An in vivo experimental study

Abstract: Objective To investigate the early bone formation in beagles with mini‐lateral window sinus floor elevation and simultaneous implant placement. Material and methods Six beagles were selected for the split‐mouth design procedures. In each animal, one maxillary recess received a 5 mm‐diameter mini‐round lateral osteotomy (test group), and the contralateral maxillary recess received a large rectangular osteotomy (10 mm long and 8 mm wide), (control group). Simultaneous implant installation was executed on bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
(59 reference statements)
2
9
0
Order By: Relevance
“…In the current application of LSFE, a common procedure for preparing the accessing window is to directly grind the lateral wall bone using the rotary diamond round bur, but the remaining lateral defect is reported to have an adverse effect on endo‐sinus bone healing (Yu & Qiu, 2017). In addition, current studies have shown that a smaller lateral window contributes to the early bone formation compared with a larger window whether undergoing grafting or not (Aldahouk et al, 2021; Zhu et al, 2021), which confirms the role of the lateral bone wall in endo‐sinus bone augmentation. Besides, the residual lateral defect caused by the round bur would lead to the compensation of graft material to fill the lateral antrostomy hole, which might affect the endo‐sinus augmentation effect of LSFE (Zhou et al, 2021; Figure 1a).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the current application of LSFE, a common procedure for preparing the accessing window is to directly grind the lateral wall bone using the rotary diamond round bur, but the remaining lateral defect is reported to have an adverse effect on endo‐sinus bone healing (Yu & Qiu, 2017). In addition, current studies have shown that a smaller lateral window contributes to the early bone formation compared with a larger window whether undergoing grafting or not (Aldahouk et al, 2021; Zhu et al, 2021), which confirms the role of the lateral bone wall in endo‐sinus bone augmentation. Besides, the residual lateral defect caused by the round bur would lead to the compensation of graft material to fill the lateral antrostomy hole, which might affect the endo‐sinus augmentation effect of LSFE (Zhou et al, 2021; Figure 1a).…”
Section: Introductionsupporting
confidence: 65%
“…A recent histomorphometric study in rabbits found that repositioning of the bone window could accelerate endo‐sinus bone generation and generate more new bone (31.28 ± 3.51% vs. 21.74 ± 2.40%; p < .05) and mature bone (27.37 ± 5.45% vs. 13.02 ± 3.69%; p < .05) at 8 weeks compared with the collagen membrane‐covered group (Moon et al, 2014), proving the osteoinductive efficacy of the lateral wall bone. Other studies assessing the effect of the size of lateral wall antrostomy on endo‐sinus bone formation also confirmed the above conclusion that lateral wall bone had a role of osteoinduction and acted as the source of osteogenesis, providing growth factors and a blood supply for bone regeneration (Aldahouk et al, 2021; Avila‐Ortiz et al, 2012; Yu & Qiu, 2017; Zhu et al, 2021). The above studies were in agreement with the results in this study, demonstrating that the repositioned bone wall would be beneficial to the graft stability, especially to the region near the bone window.…”
Section: Discussionmentioning
confidence: 69%
“…Incomplete corticalisation was shown despite bone bridging, as bony wall regeneration occurred surrounding the lateral window in both groups ( Figure 3D ). This may have been affected by the size of the lateral window [ 40 ] and insufficient healing time during the investigation of the osteogenic potential of PDRN in the early stage. Third, new bone formation and bone remodelling were observed in the augmented area in both groups without any specific side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were injected with 20 mg/kg calcein green (Sigma, USA) via the tail vein 14 and 4 days before euthanasia [ 37 ]. The undecalcified sections of right distal femur around the implants were obtained (EXAKT Cutting & Grinding System, Germany) [ 9 , 38 ].…”
Section: Methodsmentioning
confidence: 99%